Subsidising Education with Unionised Labour Markets - Florian Wöhlbier (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2002)
It is well known from the literature that a unionisation of labour markets leads to an increase in wages and a decrease in employment. However, in these models human capital formation is usually taken as given. This paper internalises the education decision and shows that a unionisation of the labour market for unskilled workers will also lead to an inefficiently low education level. We discuss the effects of an education subsidy. It will turn out that both the way of financing and the reaction of the trade union to tax rate changes are crucial for the employment and welfare effects.
urn:nbn:de:bvb:19-epub-7-8
Keywords: H20; J51; J24; 330; Human Capital; Unemployment; Subsidisation